Mukhlis Knowledge Donating Towards Employee Performance - Sukamto Sukamto; Heri Poerbantoro; Rita Andini; Tri Handayani; Dwi Retna Sulistyawati (Publikasi Indonesia, 2024)
This research aims to describe how internalizing